Cognitive Behavioral Therapy vs. Eye Movement Desensitization and Reprocessing for Treating Panic Disorder: A Randomized Controlled Trial - Horst, Ferdinand; Den Oudsten, Brenda; Zijlstra, Wobbe; de Jongh, Ad; Lobbestael, Jill; De Vries, Jolanda (Frontiers in Psychology, 2017)
Abstract Objective: Cognitive Behavioral Therapy (CBT) is an effective intervention for patients with panic disorder (PD). From a theoretical perspective, Eye Movement Desensitization and Reprocessing (EMDR) therapy could also be useful in the treatment of PD because: (1) panic attacks can be experienced as life threatening; (2) panic memories specific to PD resemble traumatic memories as seen in posttraumatic stress disorder (PTSD); and (3) PD often develops following a distressing life event. The primary objective of this Randomized Controlled Trial (RCT), was to compare EMDR therapy with CBT for PD and determine whether EMDR is not worse than CBT in reducing panic symptoms and improving Quality Of Life (QOL). Methods: Two-arm (CBT and EMDR) parallel RCT in patients with PD (N = 84). Patients were measured at baseline (T1), directly after the last therapy session (T2), and three months after ending therapy (T3). Non-inferiority testing (linear mixed model with intention-to-treat analysis) was applied. Patients were randomly assigned to 13 weekly 60-minute sessions of CBT (N = 42) or EMDR therapy (N = 42). Standard protocols were used. The primary outcome measure was severity of PD at T3, as measured with the Agoraphobic Cognitions Questionnaire (ACQ), the Body Sensations Questionnaire (BSQ), and the Mobility Inventory (MI). The secondary outcome measure was QOL, as measured with the World Health Organization Quality of Life short version (WHOQOL-Bref), at T3. Results: The severity of PD variables ACQ and BSQ showed non-inferiority of EMDR to CBT, while MI was inconclusive (adjusted analyses). Overall QOL and general health, Psychological health, Social relationships, and Environment showed non-inferiority of EMDR to CBT, while Physical health was inconclusive. Conclusion: EMDR therapy proved to be as effective as CBT for treating PD patients. Trial Registration: Dutch Trial Register, Nr. 3134 http://www.trialregister.nl/trialreg/admin/rctview.asp?TC=3134